The Effectiveness of Information Services in Overcoming Smartphone Addiction in Madrasah Students - Aditya Dio Putra; Nurussakinah Daulay (Universitas Pahlawan Tuanku Tambusai, 2022)
Smartphone addiction is a dangerous problem among students, including students at MTs Kesuma LKMD. The preliminary study found 11 students out of 38 total class VII students in the high-level smartphone addiction category. This study aims to determine the effectiveness of information services in overcoming smartphone addiction in madrasa students. The focus of this research is to overcome the level of smartphone addiction in these students through information services. This type of research is action research counseling guidance class (PTBK) with a one group pre-test and post-design model. The subjects of this study were 38 students of class VII MTs Kesuma LKMD, with a sample of 11 students, using cluster random sampling technique. The results of this study indicate that information services are effective in overcoming smartphone addiction in madrasa students, this can be seen from the results of a significant comparison, starting from the pre-research stage 89% experienced a decrease in smartphone addiction in the first cycle (71%), and obtained the category low by 52% (cycle II).